Patient-reported quality of life and toxicity in unilateral and bilateral radiotherapy for early-stage human papillomavirus associated tonsillar carcinoma. (March 2020) - McDowell, Lachlan; Casswell, Georgina; Bressel, Mathias; Gough, Karla; Drosdowsky, Allison; Coleman, Andrew; Shrestha, Sudi; D'Costa, Ieta; Fua, Tsien; Tiong, Albert; Liu, Chen; Ng, Sweet Ping; et al.
Highlights: Unilateral radiotherapy is utilised in T1-2, N0-N1 lateralised tonsillar tumours. The role of unilateral radiotherapy in more advanced nodal disease is less clear. Higher symptom burden and lower QoL was reported by patients treated with bilateral radiotherapy. In the IMRT era, bilateral treatment for tonsillar cancer may have an enduring impact on the patient. Prospective evaluation of unilateral radiotherapy with lateralised tumours and N2-3 is needed. Abstract: Purpose: The purpose of this study was to compare self-reported health-related quality of life (QoL) and symptom burden in early stage tonsillar carcinoma patients treated with unilateral (URT) and bilateral radiotherapy (BRT). Methods and materials: This is a secondary analysis of a larger study assessing patient reported outcomes in human papillomavirus (HPV) oropharyngeal cancer (OPC) patients. Recruited patients were ≥12 months from completion of radiotherapy. This analysis included only patients with T1-2, N1-2b tonsil cancer and excluded patients with base of tongue involvement or recurrent disease. QoL and patient reported toxicity was measured using the EORTC QLQ-C30 module and the MDASI-HN. Results: Patients were enrolled from November 2018 to May 2019. Of the 136 patients recruited to the main study, 43 were eligible for this substudy (22 URT, 21 BRT), with a median age and follow up of 58.2 and 3.0 years respectively. The two groups were balanced with respect to patient, tumor and treatment factors with the exception of higher rates of T2 disease (27% v 71%, p = 0.006) and more extensive GTV nodal volumes (11.0 v 25.5cc, p = 0.006) in the BRT group. BRT patients had lower global health status/QoL (84 v 69, p = 0.0005) and social functioning scores (93 vs 78, p = 0.033) on the EORTC QLQ-C30, and higher symptom severity (0.6 vs. 2.0, p = 0.001) and symptom interference scores (0.8 vs. 2.0, p = 0.010) on the MDASI-HN. Four of the six largest differences observed on MDASI-HN items were attributable to radiotherapy technique (dry mouth, mucous, difficulty swallowing/chewing and taste), with corresponding dose differences to the respective organs (contralateral parotid, oral cavity and pharyngeal constrictors). In every instance, severity of symptoms was worse on average for patients treated with BRT. Conclusions: In the highly conformal radiotherapy era, BRT in early HPV tonsillar cancer survivors has an enduring impact on long-term QoL and toxicity.